Tax Breaks and Investment - Kuder, Seba (Journal of Legal Sciences, 2022)
Iraq alerts to the fact that it is necessary to keep pace with globalization and the need to attract foreign investment, in the hope that it will find a solution or it will be possible for it to control its economic problems, the most important of which is the problem of unemployment. incentives such as tax breaks. So it is necessary to study those exemptions and study their role in encouraging foreign investment in Iraq.